Procedimientos del área de los Servicios de Atención a la Comunidad (SAC) de la Secretaría Municipal de Cereté (2023)
The Community Attention System (SAC) is responsible for attending to the community that uses the health services provided in the Municipality of Cereté, and it is this unit that serves as an interlocution between the local health department and the actors of the Social Security System, aimed at the continuous improvement of the public health service, through personalized attention to the user, promoting participation and social control, and the management for the solution of complaints, petitions and claims in a timely and efficient manner. Given this, the Secretariat of Health of the municipal mayor's office of Cereté has a process of attention to the community SAC for all those people who need help to solve their complaints, petitions and claims, therefore the objective of this work consisted in documenting the procedures of the Community Attention Service area SAC for the creation of a manual of procedures directed to officials of the Municipal Secretariat of Health of Cereté. By means of a bibliographic review on the subject and with the support of the officials of this SAC area. Thus, it was possible to document the procedures of the SAC Community Care Service area and to design the procedures manual based on the experiences of the workers and the manuals established by the Ministry of Health and Social Protection, as well as those of other territorial entities in the country. Finally, the manual was socialized to the officials of the Cereté Municipal Health Secretariat.